Performance comparison analysis of SSHMIPv6 and HMIPv6 lost packets using network simulator NS-2 - Alrashdan, Ma`en; Ismail, Mahamod; Jumari, Kasmiran; Abed, Ghassan A.; Hassan, Suhaidi (Asian Network for Scientific Information, 2011)
In today’s fast based technological growth the traditional networks are no longer capable of handling the increasing demands with the best Quality of Service (QoS) which depends on the type of service that network devices provide.The target of this study was to simulate different amount of transferred packets to show the performance of Smart Selection Hierarchical Mobile Internet Protocol version 6 (SSHMIPv6) with respect to lost packets. SSHMIPv6 environment has been simulated over NS-2 and used to evaluate the performance of SSHMIPv6 over HMIPv6 and to analyze the effect of adding multiple MAPs to serve each region.A decrease of 33% in lost packets was obtained by using three MAPs in SSHMIPv6 instead of one in HMIPv6.Therefore, the problem of scalability is resolved when the domain handles many MNs.